Niveau de stress perçu par les doctorants et stratégies de coping dysfonctionnelles - Laetitia Gérard; Marc Nagels (Recherches en Éducation, 2017)
PhD students encounter many difficulties and obstacles during their doctorate that are stress generators. How do they manage their stress? In our exploratory study, we wondered if the PhD students viewed their doctorate as a stressful experience and if they adopted behaviors that could be similar to dysfunctional coping strategies. We passed an online questionnaire with 357 PhD students. The results show that half of the PhD students assesses how high stress levels or very high. Behaviors that could be similar to dysfunctional coping strategies were observed.